2016
DOI: 10.1002/hast.625
|View full text |Cite
|
Sign up to set email alerts
|

Educating Nurses for Ethical Practice in Contemporary Health Care Environments

Abstract: Because health care professions exist to provide a good for society, ethical questions are inherently part of them. Such professions and their members can be assessed based on how effective they are in developing knowledge and enacting practices that further the health and well-being of individuals and society. The complexity of contemporary health care environments makes it important to prepare clinicians who can anticipate, recognize, and address problems that arise in practice or that prevent a profession f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
11
0
4
Order By: Relevance
“…Derived from the essays of nurses in different specialty areas and levels of education and responsibilities, they paint a panoramic picture of difficulties faced and the perceived knowledge and skills needed to practice ethically. While it is generally accepted that ethics education is very important for nurses at all levels of practice (American Association of Colleges of Nursing, 2008Nursing, , 2011Gastmans, 2002;International Council of Nurses, 2012), what this should entail and how it should be incorporated into nursing education, initial and ongoing, is less clear (Grace & Milliken, 2016;Grace et al, 2014;Peirce & Smith, 2008;Robinson et al, 2014;Zakaria, Sleem, & Seada, 2016). Findings support contemporary thinking that adequate ethics education must address three aspects foundational for moral agency-the ability to bring about a good (Grace, 2014): the development or refinement of personal and professional characteristics facilitative of moral agency, knowledge of ethics language and associated analytic tools, and the ability to influence those changes necessary to achieve the profession's goals of quality patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Derived from the essays of nurses in different specialty areas and levels of education and responsibilities, they paint a panoramic picture of difficulties faced and the perceived knowledge and skills needed to practice ethically. While it is generally accepted that ethics education is very important for nurses at all levels of practice (American Association of Colleges of Nursing, 2008Nursing, , 2011Gastmans, 2002;International Council of Nurses, 2012), what this should entail and how it should be incorporated into nursing education, initial and ongoing, is less clear (Grace & Milliken, 2016;Grace et al, 2014;Peirce & Smith, 2008;Robinson et al, 2014;Zakaria, Sleem, & Seada, 2016). Findings support contemporary thinking that adequate ethics education must address three aspects foundational for moral agency-the ability to bring about a good (Grace, 2014): the development or refinement of personal and professional characteristics facilitative of moral agency, knowledge of ethics language and associated analytic tools, and the ability to influence those changes necessary to achieve the profession's goals of quality patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The emotional experience of MD is linked to the lack of power to affect a good resolution. Moral agency-the ability to bring about a goodon the other hand has been proposed as likely to lessen MD (Grace & Milliken, 2016;Liaschenko & Peter, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The limited amount of time spent on ethical decision-making activities could also be due to APNs not feeling competent enough to fully take on the role of initiator and facilitator of ethical discussions (Van Hecke et al, 2019). As ethical decision-making skills are expected of APNs, who are in leadership positions (Grace & Milliken, 2016), it is vital that advanced practice nursing curricula focus on clinical, research, business, and legal ethics (Peirce & Smith, 2008 (Cannaerts, Gastmans, & Dierckx de Casterlé, 2014). As literature on APNs' ethical decision-making competencies is rare, further research is indicated to uncover barriers and facilitators for the full execution of this advanced practice nursing role.…”
Section: Time Spent On Activities In Rolesmentioning
confidence: 99%
“…Ethical competence is the root of the professional discipline of nursing in the sense that it is good for society. [34] For many nursing regulatory groups worldwide, competence or literacy in ethics is required for a license to practice nursing. The 9-item "ethical literacy" competency in this refined scale is similar to the "ethical practice" competency measured by the Canada's Competencies in the Context of Entry-Level Registered Nurse [35] and "prioritize people" in United Kingdom's code for Nurses, [7] such as "respects and preserves clients' rights", "promotes a safe environment for clients", "minimize the potential influence of personal values", "provides care for all clients", "Respect people's right to privacy and confidentiality".…”
Section: Study Limitationsmentioning
confidence: 99%